(untitled) (Journal of Hama University, 2026)
Introduction: Activities of daily living (ADL) are an important basic self-care skill for the general population, as well as for nursing home residents. Due to the physical changes associated with aging and comorbidities, nursing home residents may experience functional decline over time. The ability to perform ADL declines in most older adults due to changes in the functions of various organ systems. Dependence in ADL is associated with decreased quality of life and increased healthcare costs. Objective: To assess the ability of older adults residing in nursing homes in Lattakia to perform ADL. Research Materials and Methods: A descriptive study was conducted after determining the appropriate sample size for the study, which was 30 elderly residents. The residents were randomly selected from elderly residents of nursing homes in Lattakia (Dar Al Raha, Dar Al Ber and Social Services, and Dar Al Mowasat Al Islamiya) during June and July 2024. Data were collected using two tools: a demographic data form designed by the researcher based on a review of relevant references, and the Barthel Index (BI) to measure activities of daily living. The data were transcribed and then analyzed using the Statistical Package for the Social Sciences (SPSS). Results: The results showed that the largest percentage of the sample (63.3%) was dependent on others, while approximately a quarter of the sample (23.3%) was severely dependent on others. None of the sample members were fully independent according to the Barthel Index. Recommendations: It is recommended to conduct training programs for elderly residents of nursing homes to enhance their performance of daily living activities, and to conduct a study to evaluate the impact of motor rehabilitation programs on the elderly’s ability to perform activities of daily living.